Halal Ecotourism Based on Harmony between Religion and Local Culture in the Villages Supporting Ujung Kulon National Park (UKNP) in Banten - La Tora, Rusdan; Doenkersgoed, Joella van; Sty., Moch. Bangga Diwa Abianta; Yusuf, Thomas Muhammad (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2025)
Indonesia has great potential for developing ecotourism, but this sector has not been fully exploited. Low awareness of conservation and welfare issues among communities surrounding Ujung Kulon National Park (UKNP) often lead to harmful activities, requiring a comprehensive approach that involves socio-cultural and religious aspects. This study aims to find a model of halal ecotourism based on religious harmony and local culture among the communities surrounding UKNP Banten. The method used is descriptive qualitative, sourced from document reviews and researcher observation data in rural Banten. The results of the study show that the Islam of the Tamanjaya Village community (a buffer village of UKNP) is traditional in nature, accommodating, and integrated with local wisdom. Local traditions positively contribute to nature conservation (e.g., prohibition of tree felling), enriching the potential for halal ecotourism along with natural resources (Peucang Island, Cikacang Waterfall) and local culture (Rengkong Dance, Lesung Dance). However, the development of ecotourism is hampered by inadequate infrastructure, limited community knowledge, and the need for innovation in management and marketing. In conclusion, the buffer zone villages of UKNP are very suitable for development as halal ecotourism based on harmony between religion and local culture by overcoming the challenges of infrastructure, community empowerment, and marketing. This research makes an important contribution in three fields of study—ecotourism, ecology, and local religion/culture—by offering a novel model of halal ecotourism based on religious and local cultural harmony.